Progress on Precise Regulation of Vascular Intimal Repair by a Surface Coating of Vascular Stent - Liu, Shihui; Zhi, Junchao; Li, Shijie; Song, Zhuoyue; Gong, Tao; Pan, Changjiang; Tang, Chunzhi; Xu, Nenggui; Liu, Tao (Current Drug Delivery, 2021)
In the past few decades, drug-eluting stents have made significant contributions to the treatment of coronary heart disease. However, due to the delayed healing of endothelial injuries caused by antiproliferative drugs and insufficient biocompatibility of vascular stent materials, late in-stent thrombosis and restenosis remain major challenges. Surface modification of cardiovascular materials to construct a biological functional layer that can regulate the behavior of blood and vascular cells is an effective way to improve the clinical performance of vascular stents. This paper reviewed the common methods of surface bio-functional modification of cardiovascular materials and especially proposed that take advantage of the new concept of precision medicine, as well as the precise and orderly regulation properties of cardiovascular disease-related gene fragments on vascular biological response behavior, the construction of gene-eluting stents which can in-situ regulate vascular intimal repair at the molecular and genetic level will become an important research direction in the future.
Keywords: restenosis